Congenital vertical talus open reduction surgery: Technique description and our twenty-years personal experience - Federica De Rosa; Giorgio Cecarini; Cristina Lazzotti; Daniele Sini; Carlo Origo (PAGEPress Publications, 2022)
Congenital vertical talus foot is a complex deformity, characterized by a dislocation of the talus-calcanear navicular joint. It is a rare form of congenital flat foot, where the hindfoot is valgus and equine, the midfoot dorsiflexed and the forefoot abducted. Regardless of the type of classification, the therapeutic approach and prognosis must take into account the functionality and motility of the foot. Initial treatment is manipulative. After 3 months of age, it is possible to think about soft tissue surgery. In this study, we present congenital vertical talus feet treated at the Pediatric Orthopedics Department of SS. Antonio Biagio and Cesare Arrigo Children's Hospital of Alessandria from 1995 to 2022. All 8 patients (12 feet) underwent through the surgical operation technique of open reduction described by Tachdjian and further reviewed and subjected to the American Orthopaedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot Score. The mean follow up is 13 years. Global functional result was good and surgery allowed the growth of the foot, which would otherwise be blocked by an ax that is the vertical talus. Questioned remotely, all patients perform sporting activities and wear normal footwear.